DYNAMICS OF NERVE CELLS : II. THE TEMPERATURE COEFFICIENTS OF CARBON DIOXIDE PRODUCTION BY THE HEART GANGLION OF LIMULUS POLYPHEMUS. - Garrey, Walter E. (The Rockefeller University Press, 1920)
1. It is possible to determine by the colorimetric method the rate of production of carbon dioxide by the cardiac ganglion of Limulus. 2. Carbon dioxide formation in the cardiac ganglion was found to run parallel to the rate of heart beat for different temperatures. 3. The conclusion seems justified that the rate of cardiac rhythm of Limulus depends upon a chemical reaction in the nerve cells of the cardiac ganglion and that this reaction is associated with the production of carbon dioxide since the rate of beat and the rate of CO(2) production are similarly affected by changes in temperature.